Fluid Geochemistry within the North China Craton: Spatial Variation and Genesis. (25th October 2021) - Chang, Lu; Ying, Li; Zhi, Chen; Zhaofei, Liu; Yuanxin, Zhao; Le, Hu
Abstract : The North China Craton (NCC) is a typical representative of the ancient destruction craton. Numerous studies have shown that extensive destruction of the NCC occurred in the east, whereas the western part was only partially modified. The Bohai Bay Basin is in the center of the destruction area in the eastern NCC. Chemical analyses were conducted on 122 hot spring samples taken from the eastern NCC and the Ordos Basin. The δ 2 H and δ 18 O in water, δ 13 C in CO2, and 3 He/ 4 He and 4 He/ 20 Ne ratios in gases were analyzed in combination with chemical analyses of water in the central and eastern NCC. The results showed an obvious spatial variation in chemical and isotopic compositions of the geofluids in the NCC. The average temperature of spring water in the Trans-North China Block (TNCB) and the Bohai Bay Basin was 80.74°C, far exceeding that of the Ordos Basin of 38.43°C. The average δ D in the Eastern Block (EB) and the TNCB were −79.22‰ and −84.13‰, respectively. The He isotope values in the eastern region (TNCB and EB) ranged from 0.01 to 2.52, and the rate of contribution of the mantle to He ranged from 0 to 31.38%. δ 13 C ranged from −20.7 to −6.4‰ which indicated an organic origin. The chemical compositions of the gases in the EB showed that N2 originated mainly from the atmosphere. The EB showed characteristics of a typical gas subduction zone, whereas the TNCB was found to have relatively small mantle sources. The reservoir temperatures in the Ordos Basin and the eastern NCC (EB and TNCB) calculated by the K-Mg temperature scale were 38.43°C and 80.74°C, respectively. This study demonstrated clear spatial variation in the chemical and isotopic compositions of the geofluids in the NCC, suggesting the presence of geofluids from the magmatic reservoir in the middle-lower crust and that active faults played an important role in the transport of mantle-derived components from the mantle upwards.